Abstracts from the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GR APP A) Trainees Symposium. Issue 4 (December 2014) - Unknown
On July 11, 2014, 27 fellows and trainees from around the world presented abstracts at the Trainees Symposium at the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) annual meeting in New York City. The symposium was developed as an opportunity for trainees and fellows in rheumatology and dermatology to develop their research skills through presentation and discussion of their work. The topics of the poster presentations ranged widely, reflecting many aspects of GRAPPA's work. Subjects included comorbidities, nail disease, screening tools, incidence and relevance studies, and translational research. Before the meeting, senior GRAPPA members ranked the abstracts, and the top four were invited to present their findings orally with a 15-minute slide presentation. The others were invited to speak for 5 to 7 minutes from posters based on their findings. This year, the four selected to give oral presentations were Drs. Deepak Jadon (UK), Will Tillett (UK), Lihi Eder (Canada/Israel), and Agnes Szentpetery (Ireland). For the first time, the 2014 GRAPPA Annual Meeting and Fellows Symposium included a cohort of fellows from the Spondyloarthritis Treatment and Research Network (SPARTAN). Four SPARTAN fellows shared the podium with the GRAPPA oral presenters, and another dozen SPARTAN fellows presented posters alongside the GRAPPA poster presenters. Christopher Ritchlin, M.D., M.P.H., of the University of Rochester School of Medicine, founded the GRAPPA Trainees Symposium in 2008. It has been a popular addition to the GRAPPA annual meeting ever since. Here we present a selection of the abstracts submitted by the GRAPPA trainees and fellows from 2014.